Application of Queuing Systems: a Case Study of the Outpatient . Department of Kwahu Government Hospital, Atibie - Semordzi, Mawuli (2011)
A Thesis submitted to the Department of Mathematics, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the award of Master of Science degree in Industrial Mathematics.